2012
DOI: 10.1590/s0066-782x2012005000099
|View full text |Cite
|
Sign up to set email alerts
|

Papel do ecocardiograma na avaliação ventricular do coração transplantado versus rejeição cardíaca

Abstract: Background: Heart transplantation is an alternative for individuals with end-stage heart disease. However, episodes of heart rejection (HR) are frequent and increase morbidity and mortality, requiring the use of an accurate non-invasive exam for their diagnosis, since endomyocardial biopsy (EMB) is not a complication-free procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Miguel et al discovered IMP in HTX patients with and without rejection were significantly higher than that in healthy control group. In addition, IMP in HTX patients with rejection was higher than that in HTX patients without rejection, but not reaching statistical level, [ 49 ]. Burgess et al demonstrated an absence of significant change in IMP between rejection group and Non-rejection group.…”
Section: Discussionmentioning
confidence: 99%
“…Miguel et al discovered IMP in HTX patients with and without rejection were significantly higher than that in healthy control group. In addition, IMP in HTX patients with rejection was higher than that in HTX patients without rejection, but not reaching statistical level, [ 49 ]. Burgess et al demonstrated an absence of significant change in IMP between rejection group and Non-rejection group.…”
Section: Discussionmentioning
confidence: 99%